PSYCHOLOGICAL CONDITIONS AND COMMUNICATION LOAD OF EDUCATORS ON DIGITAL STRESS - Widya Parimita (JURNAL ADMINISTRASI KANTOR, 2022)
This study aims to describe, calculate and analyze the effect of Social Pressure, Communication Load, fear of being left behind on Lecturer's Perceived Stress. The model used in this study is a causal model or relationship and influence, or also known as path analysis. To test the hypothesis that will be proposed in this study, the model fit analysis technique used is SEM (Structural Equation Modeling) which is operated using the SMARTPLS 3.0 program. The results of the study prove that there is a positive and significant influence between Social Pressure, Communication Load, fear of being left behind on Perceived Stress. The results of this study are expected to be used as library materials and information in the development of science, especially in the field of human resource management and especially in developing theories in overcoming digital stress for both lecturers and other readers.